Accumulation, subcellular distribution, and ecological risk assessment of Pb and Cd in Bellamya aeruginosa from the Xiangjiang River, China. Issue 4 (20th April 2020) - Liu, Jun; Huang, Wei; Li, Zhiliang; Hu, Jingsong; Zhu, Yunhua; Xie, Hongyan; Peng, Cuiying
ABSTRACT: Field investigation and laboratory experiments were conducted to study the Pb and Cd tolerance mechanism of Bellamya aeruginosa from the Xiangjiang River. B. aeruginosa were collected from the middle reaches of the Xiangjiang River, and their Pb and Cd accumulation and subcellular distribution, as well as the related ecological risks, were analysed. Results showed significant differences between Pb and Cd accumulation and distribution in B. aeruginosa . Cd concentration was distributed in the following decreasing order: visceral mass > mantle > foot > shell, with the visceral mass and mantle being the main Cd accumulation sites. The shell was the main part accumulating Pb in B. aeruginosa, with Pb not being detected in soft tissues. Differential centrifugation revealed Cd subcellular distribution, i.e. lysosomes and mitochondria were the important accumulation and effect sites of Cd in B. aeruginosa cells . Cd subcellular distribution effectively reduced Cd damage on the nuclei, which improved the Cd tolerance of B. aeruginosa . The single factor pollution ( Pi ) and metal pollution (MPI) indices showed that the middle reaches of the Xiangjiang River had been seriously polluted by Pb and Cd. Cd pollution was particularly serious, accumulating in B. aeruginosa, which constituted a food safety hazard to humans.